Coal-based hard carbon negative electrode material, preparation method thereof and sodium ion battery

Through liquid phase mixing of alkali and coal powder and low-temperature carbonization activation, combined with pickling and ash removal, the problems of high ash content and low electrochemical performance of coal-based hard carbon negative electrode materials are solved, and efficient preparation of coal-based hard carbon negative electrode materials are achieved. Improved sodium storage capacity and platform capacity.

CN119284875APending Publication Date: 2025-01-10GUANGDONG KAIJIN NEW ENERGY TECH CORP LTD

Patent Information

Application Number
CN202411400107.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing coal-based hard carbon negative electrode material preparation process has the problems of high ash content and low electrochemical performance, and harmful acids need to be used during the ash removal process, which affects the safety of the environment and equipment.

Method used

The alkali and coal powder liquid are mixed, and the ash is removed after low-temperature carbonization and activation, forming coal-based hard carbon with a low specific surface area. The alkali molten state reacts with minerals in the coal powder to form acid-soluble substances to achieve ash removal and pore-making to improve sodium storage capacity and platform capacity.

Benefits of technology

Coal-based hard carbon negative electrode material with low ash content, high specific capacity and good Coulomb efficiency for the first time was obtained, which simplified the process flow, reduced the use of acid substances, and improved the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284875A_ABST
    Figure CN119284875A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery material preparation, and provides a coal-based hard carbon negative electrode material, a preparation method thereof and a sodium ion battery. The preparation method of the coal-based hard carbon negative electrode material comprises the following steps: (I) uniformly mixing pulverized coal, alkali and water, and drying to obtain a mixture, wherein the mass ratio of the pulverized coal to the alkali to the water is 1: (0.01-0.8): (1-10); (II) performing low-temperature carbonization and activation on the mixture in a first inert atmosphere to obtain a first precursor, wherein the low-temperature carbonization and activation temperature is 450-1000 DEG C; (III) carrying out acid pickling, water washing and drying on the first precursor to obtain a second precursor; and (IV) carbonizing the second precursor in a second inert atmosphere. The coal-based hard carbon negative electrode material prepared by the invention has relatively low ash content and a proper closed-pore structure, and shows relatively high specific capacity and first coulombic efficiency when being used as a sodium-ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery material preparation, and in particular to a coal-based hard carbon negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] Lithium-ion batteries have been successfully used in commercial applications, but due to the abundance of lithium, they are difficult to meet the growing demand for energy storage market, and the development of new energy storage methods is urgent. Sodium and lithium are in the same main group, with similar chemical properties and storage mechanisms. The abundance of sodium is 423 times that of lithium, and the production process of sodium-ion batteries is similar to that of lithium-ion batteries. Therefore, sodium-ion batteries are expected to stand out among many new secondary batteries.

[0003] In the field of negative electrode materials, graphite is often used in lithium-ion batteries. Larger than the radius of lithium ions The former is difficult to embed into the graphite interlayer, and the interlayer compound formed by sodium ions and graphite is in a thermodynamically unstable state, resulting in a low sodium storage capacity of the graphite negative electrode. Among the reported alloy, conversion, embedding and organic sodium ion battery negative electrode materials, hard carbon has commercial prospects due to its advantages such as low sodium storage potential, high capacity and low cost.

[0004] The precursors of hard carbon include biomass, polymers, coal, etc. Biomass has seasonal and regional characteristics, while polymers are expensive. Based on my country's abundant coal resources, the development of low-cost coal-based hard carbon can better highlight the advantages of sodium-ion batteries. However, there are still some technical difficulties in the development of coal-based hard carbon that need to be solved. First, coal contains a high ash content, which will affect the electrochemical performance and safety of the battery; second, the large number of aromatic rings in coal causes the interlayer spacing of hard carbon to be small, thereby showing a lower sodium storage capacity. In terms of ash removal, physical methods, chemical methods and physical-chemical combined methods are often used, among which chemical methods require mixed acid (hydrochloric acid, hydrofluoric acid, nitric acid, etc.) or multi-stage acid treatment to effectively remove minerals such as pyrite and aluminosilicates. For example, CN113381013A crushes coal and then uses hydrochloric acid and hydrofluoric acid multi-stage acid washing to remove ash. The initial ash removal requires a large amount of acid, and the oxidizing acid poses a threat to people, equipment, and the environment. It is easy to cause carbon modification and increase the burden of wastewater treatment, which is limited in practical application. In terms of improving electrochemical performance, technologies such as process control (carbonization temperature, heating rate, gas flow rate, etc.), precursor modification (oxidation, cross-linking, composite, etc.), structural engineering (activation, template, etc.), and interface engineering (doping, coating, etc.) have emerged. For example, CN118183739A constructs closed holes by first creating holes and then coating them with heterogeneous materials. The process is cumbersome, and exploring simple and efficient processes will be conducive to large-scale production.

[0005] In view of the above problems in the preparation of coal-based hard carbon, how to develop a simple and efficient preparation process of coal-based hard carbon is an urgent problem to be solved in the current field of negative electrode materials. Summary of the invention

[0006] In view of the above problems, the object of the present invention is to provide a coal-based hard carbon and a preparation method thereof and a sodium ion battery. The coal-based hard carbon prepared by the present invention has a low ash content and a suitable closed-pore structure, and exhibits a high specific capacity and first coulombic efficiency when used as a negative electrode material for a sodium ion battery.

[0007] To achieve the above object, the first aspect of the present invention provides a method for preparing a coal-based hard carbon negative electrode material, comprising the steps of:

[0008] (I) uniformly mixing coal powder, alkali and water and drying to obtain a mixture, wherein the mass ratio of coal powder, alkali and water is 1:0.01-0.8:1-10;

[0009] (II) subjecting the mixed material to low-temperature carbonization activation in a first inert atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 450° C. to 1000° C.;

[0010] (III) acid-washing, water-washing and drying the first precursor to obtain a second precursor;

[0011] (IV) carbonizing the second precursor in a second inert atmosphere.

[0012] Compared with the prior art, the present invention utilizes alkali as both a pore-forming agent and an ash-removing aid, and the coal powder and alkali are mixed in the liquid phase to make the alkali uniformly distributed in the coal powder, and the mass ratio of coal powder, alkali and water is further adjusted to 1:0.01~0.8:1~10, which can ensure the subsequent pore-forming and ash-removing effects of the alkali, and at the same time, a coal-based hard carbon negative electrode material with a low specific surface area can be obtained after carbonization. Specifically, during the low-temperature carbonization activation process, the alkali etches the carbon skeleton to form a large number of open micropores, which are converted into closed pores during carbonization, thereby increasing the sodium storage capacity and platform capacity share of the coal-based hard carbon negative electrode material. In addition, the alkali is in a molten state at 450℃~1000℃, and the molten alkali can react with minerals such as silicon and aluminum in the coal powder to generate acid-soluble substances, which can be effectively removed by acid washing and water washing, and the coal-based hard carbon negative electrode material prepared by the present invention exhibits a high specific capacity and first coulomb efficiency when used as a negative electrode material for sodium ion batteries.

[0013] In some embodiments, the coal powder is obtained by coarsely crushing, drying and pulverizing the raw coal.

[0014] In some embodiments, the raw coal is selected from at least one of anthracite, bituminous coal, sub-bituminous coal, and lignite.

[0015] In some embodiments, the particle size D of the raw coal isv 100 is 0.1cm~1.0cm;

[0016] In some embodiments, the drying temperature of the raw coal is 50°C to 100°C, and the drying time is 12h to 72h;

[0017] In some embodiments, the raw coal is pulverized by at least one of air flow milling, roller milling and mechanical milling.

[0018] In some embodiments, the base is selected from at least one of sodium hydroxide and potassium hydroxide;

[0019] In some embodiments, the mixing is performed in a stirrer, the rotation speed of the stirrer is 50 r / min to 500 r / min, and the stirring time is 0.5 h to 12 h.

[0020] In some embodiments, the holding time of low-temperature carbonization activation is 0.5 h to 10 h.

[0021] In some embodiments, the heating rate of low-temperature carbonization activation is 0.1° C. / min to 10° C. / min.

[0022] In some embodiments, the acid used for pickling is selected from hydrochloric acid.

[0023] In some embodiments, the effective amount of the acid is 36 wt.% to 38 wt.%.

[0024] In some embodiments, the pickling temperature is 50° C. to 90° C., and the pickling time is 4 h to 24 h.

[0025] In some embodiments, the water washing temperature is 50° C. to 90° C., and the water washing time is 0.5 h to 5 h.

[0026] In some embodiments, the carbonization temperature is 1100° C. to 1600° C., and the holding time is 1 h to 10 h.

[0027] In some embodiments, the heating rate of carbonization is 0.1° C. / min to 10° C. / min.

[0028] In some embodiments, in step (I) and step (III), the drying temperature is independently 50° C. to 100° C., and the drying time is independently 12 h to 72 h.

[0029] In some embodiments, the first inert atmosphere and the second inert atmosphere are each independently selected from at least one of nitrogen, argon, and helium.

[0030] In some embodiments, step (I) comprises first dissolving alkali in water, then adding coal powder, stirring evenly, and then drying to obtain a mixture.

[0031] In some embodiments, the effective amount of base is greater than or equal to 85 wt.%.

[0032] In some embodiments, the particle size D of the coal powder is v 50 is 2μm~15μm.

[0033] In some embodiments, the acid washing comprises reacting the first precursor, acid and water and filtering once to obtain an acid washed material, and the water washing comprises repeatedly washing the acid washed material in water and filtering twice until the filtrate is neutral.

[0034] In some embodiments, the mass ratio of the first precursor, the acid, and water is 1:0.01-0.8:1-10.

[0035] In some embodiments, the mass ratio of the pickling material to water is 1:1-25.

[0036] In some embodiments, the primary filtration and the secondary filtration are each independently selected from negative pressure filtration, positive pressure filtration, or centrifugal filtration;

[0037] The second aspect of the present invention provides a coal-based hard carbon negative electrode material, which is prepared by the aforementioned preparation method.

[0038] A third aspect of the present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is the aforementioned coal-based hard carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a preparation flow chart of Example 2 of the present invention.

[0040] Figure 2 This is a SEM image of the coal-based hard carbon negative electrode material prepared in Example 2 of the present invention.

[0041] Figure 3 Schematic diagram of the evolution of the material microstructure under the process conditions of Comparative Example 2, Comparative Example 1 and Example 2 of the present invention respectively. DETAILED DESCRIPTION

[0042] The present invention provides a sodium ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte, wherein the negative electrode material is a coal-based hard carbon negative electrode material of the present invention. The coal-based hard carbon negative electrode material of the present invention can be used alone or mixed with other negative electrode materials (such as expanded graphite, graphite intercalation compounds and soft carbon, etc.). The preparation method of the coal-based hard carbon negative electrode material of the present invention comprises the steps of:

[0043] (I) uniformly mixing coal powder, alkali and water and drying the mixture;

[0044] (II) subjecting the mixed material to low-temperature carbonization activation in a first inert atmosphere to obtain a first precursor;

[0045] (III) acid-washing, water-washing and drying the first precursor to obtain a second precursor;

[0046] (IV) Carbonizing the second precursor in a second inert atmosphere to obtain a coal-based hard carbon negative electrode material.

[0047] In step (I), the alkali is first dissolved in water, then added to the coal powder, stirred evenly, and then dried to obtain a mixture. The alkali of the present invention is first dissolved in water and then mixed with the coal powder, which can ensure that the two are mixed evenly, thereby improving the pore-forming and ash-removing effects of the alkali in the coal powder during the subsequent low-temperature carbonization activation process.

[0048] The alkali can be selected from at least one of sodium hydroxide and potassium hydroxide. The effective content of the alkali is greater than or equal to 85wt.%. As an example, the effective content of the alkali can be, but is not limited to, 85wt.%, 86wt.%, 87wt.%, 88wt.%, 89wt.%, 90wt.%, 92wt.%, 94wt.%, 96wt.%, 98wt.%, 99wt.%. The water is specifically tap water or purified water. The greater its resistivity, the less impurities it contains, which can effectively avoid the introduction of other impurities when the coal powder and the alkali are mixed in the liquid phase, thereby reducing the adverse effects on the resulting coal-based hard carbon negative electrode material. The particle size D of the coal powder v 50 is 2 μm to 15 μm. As an example, the particle size D of the coal powder is v 50 can be, but is not limited to, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, and 15 μm. Coal powder is obtained by coarsely breaking, drying, and pulverizing raw coal.

[0049] The raw coal can be selected from at least one of anthracite, bituminous coal, sub-bituminous coal and lignite. v 100 is 0.1 cm to 1.0 cm. As an example, the particle size D of the raw material is roughly crushed. v100 may be, but is not limited to, 0.1 cm, 0.2 cm, 0.3 cm, 0.4 cm, 0.5 cm, 0.6 cm, 0.7 cm, 0.8 cm, 0.9 cm, and 1.0 cm. The drying temperature of the raw coal is 50°C to 100°C. In some technical solutions, the drying temperature of the raw coal is 65°C to 96°C. In some technical solutions, the drying temperature of the raw coal is 82°C to 93°C. In some technical solutions, the drying temperature of the raw coal is 85°C. As an example, the drying temperature of the raw coal may be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, and 100°C. The drying time of raw coal is 12h~72h. In some technical solutions, the drying time of raw coal is 20h~68h. In some technical solutions, the drying time of raw coal is 22h~58h. In some technical solutions, the drying time of raw coal is 24h. As an example, the drying time of raw coal can be, but not limited to, 12h, 15h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 40h, 50h, 60h, 70h, 72h. The method of raw coal pulverization includes at least one of air flow mill, roller mill and mechanical mill.

[0050] The mass ratio of coal powder, alkali and water is 1:0.01~0.8:1~10. In some technical schemes, the mass ratio of coal powder, alkali and water is 1:0.08~0.6:1~7. In some technical schemes, the mass ratio of coal powder, alkali and water is 1:0.1~0.5:1~5. In some technical schemes, the mass ratio of coal powder, alkali and water is 1:0.3:1.5. As an example, the mass ratio of coal powder, alkali and water can be, but is not limited to, 1:0.01:1, 1:0.05:1, 1:0.08:1, 1:0.1:1, 1:0.2:1, 1:0.3:1, 1:0.4:1, 1:0.5:1, 1:0.6:1, 1:0.7:1, 1:0.8:1, 1:0.01:1.5, 1:0.05:1.5, 1:0.08:1.5, 1:0. 1:1.5, 1:0.2:1.5, 1:0.3:1.5, 1:0.4:1.5, 1:0.5:1.5, 1:0.6:1.5, 1:0.7:1.5, 1:0.8:1.5, 1:0.01:2, 1:0.05:2, 1:0.08:2, 1:0.1:2, 1:0.2:2, 1:0.3:2, 1:0.4:2, 1:0.5:2, 1:0.6:2 , 1:0.7:2, 1:0.8:2, 1:0.01:4, 1:0.05:4, 1:0.08:4, 1:0.1:4, 1:0.2:4, 1:0.3:4, 1:0.4:4, 1:0.5:4, 1:0.6:4, 1:0.7:4, 1:0.8:4, 1:0.01:8, 1:0.05:8, 1:0.08:8, 1:0.1:8, 1:0.2:8 , 1:0.3:8, 1:0.4:8, 1:0.5:8, 1:0.6:8, 1:0.7:8, 1:0.8:8, 1:0.01:10, 1:0.05:10, 1:0.08:10, 1:0.1:10, 1:0.2:10, 1:0.3:10, 1:0.4:10, 1:0.5:10, 1:0.6:10, 1:0.7:10, 1:0.8:10. Mixing coal powder, alkali and water in a mass ratio of 1:0.01-0.8:1-10 can ensure the alkali etching pore-forming effect on the coal powder carbon skeleton during the low-temperature carbonization activation process. At the same time, the alkali can also react with minerals such as silicon and aluminum in the coal powder to ensure its ash removal effect.

[0051] The mixing of coal powder, alkali and water can be carried out in a mixer, and the speed of the mixer is 50r / min to 500r / min. In some technical solutions, the speed of the mixer is 80r / min to 460r / min. In some technical solutions, the speed of the mixer is 110r / min to 380r / min. In some technical solutions, the speed of the mixer is 200r / min. As an example, the speed of the mixer can be, but is not limited to, 50r / min, 80r / min, 100r / min, 120r / min, 140r / min, 160r / min, 180r / min, 200r / min, 220r / min, 240r / min, 260r / min, 280r / min, 300r / min, 350r / min, 400r / min, 450r / min, 500r / min. The stirring time is 0.5h to 12h. In some technical solutions, the mixing time is 1h to 10h. In some technical solutions, the mixing time is 1.5 to 6h. In some technical solutions, the mixing time is 2h. As an example, the stirring time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h.

[0052] After the coal powder, alkali and water are evenly mixed, they are dried to obtain a mixture, so as to facilitate the subsequent low-temperature carbonization activation step. The drying can be carried out in an oven, and the drying temperature is 50°C to 100°C. In some technical schemes, the drying temperature is 62°C to 94°C. In some technical schemes, the drying temperature is 78°C to 88°C. In some technical schemes, the drying temperature is 85°C. As an example, the drying temperature can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, and 100°C. The drying time is 12h to 72h. In some technical schemes, the drying time is 18h to 64h. In some technical schemes, the drying time is 20h to 58h. In some technical schemes, the drying time is 24h. As an example, the drying time can be but is not limited to 12h, 14h, 15h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, and 72h.

[0053] In step (II), the temperature of low-temperature carbonization activation is 450°C to 1000°C, in some technical solutions, the temperature of low-temperature carbonization activation is 485°C to 960°C, in some technical solutions, the temperature of low-temperature carbonization activation is 515°C to 865°C, in some technical solutions, the temperature of low-temperature carbonization activation is 630°C to 780°C, and in some technical solutions, the temperature of low-temperature carbonization activation is 700°C. As an example, the temperature of low-temperature carbonization activation can be, but is not limited to, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, and 1000°C. Alkali can etch the coal powder carbon skeleton at 450°C to 1000°C to form a large number of open micropores. In addition, the alkali is in a molten state at this temperature and can react with minerals such as silicon and aluminum in the coal powder to achieve the effect of removing ash.

[0054] The holding time of low-temperature carbonization activation is 0.5h~10h. In some technical solutions, the holding time of low-temperature carbonization activation is 1h~8h. In some technical solutions, the holding time of low-temperature carbonization activation is 2h~6h. In some technical solutions, the holding time of low-temperature carbonization activation is 2h. As an example, the holding time of low-temperature carbonization activation can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. If the holding time is too short, the alkali etching of the carbon skeleton is insufficient, which affects the pore formation and the ash removal effect; if the holding time is too long, the pore size of the generated pores will be further increased, affecting the closure during high-temperature carbonization, and even excessive etching will cause the collapse of the carbon skeleton.

[0055] The heating rate of low-temperature carbonization activation is 0.1°C / min to 10°C / min. In some technical schemes, the heating rate of low-temperature carbonization activation is 3°C / min to 8°C / min. In some technical schemes, the heating rate of low-temperature carbonization activation is 5°C / min. As an example, the heating rate of low-temperature carbonization activation can be, but is not limited to, 0.1°C / min, 0.4°C / min, 0.8°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min. The low-temperature carbonization activation is carried out in an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, argon and helium.

[0056] In step (III), the acid used for pickling is selected from hydrochloric acid, and the ash of the first precursor obtained by low-temperature carbonization activation can be effectively removed by washing with hydrochloric acid. The effective content of the acid is 36wt.% to 38wt.%. As an example, the effective content of the acid can be but is not limited to 36wt.%, 37wt.%, and 38wt.%. Pickling includes filtering the first precursor, acid and water once after reacting them to obtain a pickling material. The mass ratio of the first precursor, acid and water is 1:0.01 to 0.8:1 to 10. In some technical schemes, the mass ratio of the first precursor, acid and water is 1:0.05 to 0.6:1 to 8, in some technical schemes, the mass ratio of the first precursor, acid and water is 1:0.1 to 0.6:1 to 6, and in some technical schemes, the mass ratio of the first precursor, acid and water is 1:0.6:1.5. As an example, the mass ratio of the first precursor, the acid and the water can be, but is not limited to, 1:0.01:1, 1:0.05:1, 1:0.08:1, 1:0.1:1, 1:0.2:1, 1:0.3:1, 1:0.4:1, 1:0.5:1, 1:0.6:1, 1:0.7:1, 1:0.8:1, 1:0.01:1.5, 1:0.05:1.5, 1:0.08:1.5, 1:0.1:1.5, 1:0.2:1.5, 1:0. 3:1.5、1:0.4:1.5、1:0.5:1.5、1:0.6:1.5、1:0.7:1.5、1:0.8:1.5、1:0.01:2、1:0.05:2、1:0.08:2、1:0.1:2、1:0.2:2、1:0.3:2、1:0.4:2、1:0.5:2、1:0.6:2、1:0.7:2、1:0.8:2、1:0.01:4、1:0.05:4、1:0.08:4、 1:0.1:4、1:0.2:4、1:0.3:4、1:0.4:4、1:0.5:4、1:0.6:4、1:0.7:4、1:0.8:4、1:0.01:6、1:0.05:6、1:0.08:6、1:0.1:6、1:0.2:6、1:0.3:6、1:0.4:6、1:0.5:6、1:0.6:6、1:0.7:6、1:0.8:6、1:0.01:8、1:0.05:8、1 :0.08:8, 1:0.1:8, 1:0.2:8, 1:0.3:8, 1:0.4:8, 1:0.5:8, 1:0.6:8, 1:0.7:8, 1:0.8:8, 1:0.01:10, 1:0.05:10, 1:0.08:10, 1:0.1:10, 1:0.2:10, 1:0.3:10, 1:0.4:10, 1:0.5:10, 1:0.6:10, 1:0.7:10, 1:0.8:10.The pickling temperature is 50°C to 90°C. In some technical solutions, the pickling temperature is 70°C. As an example, the pickling temperature can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C. The pickling time is 4h to 24h. In some technical solutions, the pickling time is 6h. As an example, the pickling time can be, but is not limited to, 4h, 5h, 6h, 7h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, 24h. The primary filtration can be negative pressure filtration, positive pressure filtration or centrifugal filtration.

[0057] The water used for water washing can be tap water or purified water, and tap water or purified water is used for washing to remove the residual acid and other water-soluble impurities in the pickling material. Water washing includes repeatedly washing the pickling material in water and filtering it twice until the filtrate is neutral. The mass ratio of the pickling material to water is 1:1-25. In some technical schemes, the mass ratio of the pickling material to water is 1:1-20. In some technical schemes, the mass ratio of the pickling material to water is 1:2-18. In some technical schemes, the mass ratio of the pickling material to water is 1:4. As an example, the mass ratio of the pickling material to water can be, but is not limited to, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:8, 1:10, 1:12, 1:14, 1:16, 1:18, 1:20, 1:22, 1:24, 1:25. The water washing temperature is 50°C to 90°C. In some technical solutions, the water washing temperature is 70°C. As an example, the water washing temperature can be, but is not limited to, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C. The water washing time is 0.5h to 5h. In some technical solutions, the water washing time is 4h. As an example, the water washing time can be, but is not limited to, 0.5h, 1h, 2h, 3h, 4h, 5h. The secondary filtration can be negative pressure filtration, positive pressure filtration or centrifugal filtration.

[0058] The first precursor is dried after acid washing, primary filtration, water washing and secondary filtration to facilitate the subsequent carbonization step. Drying can be carried out in an oven. The drying temperature is 50°C to 100°C. In some technical schemes, the drying temperature is 54°C to 96°C. In some technical schemes, the drying temperature is 75°C to 88°C. In some technical schemes, the drying temperature is 85°C. As an example, the drying temperature can be but is not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, and 100°C. The drying time is 12h to 72h. In some technical schemes, the drying time is 14h to 69h. In some technical schemes, the drying time is 32h to 42h. In some technical schemes, the drying time is 24h. As an example, the drying time can be but is not limited to 12h, 14h, 16h, 18h, 20h, 22h, 24h, 26h, 28h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, and 72h.

[0059] In step (IV), the second precursor obtained in step (III) is carbonized to obtain the coal-based hard carbon negative electrode material of the present invention. The carbonization temperature is 1100°C to 1600°C. In some technical schemes, the carbonization temperature is 1350°C to 1450°C. In some technical schemes, the carbonization temperature is 1400°C. As an example, the carbonization temperature may be, but is not limited to, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C. The insulation time is 1h to 10h. In some technical schemes, the insulation time is 1.5h to 8h. In some technical schemes, the insulation time is 2h. As an example, the insulation time may be, but is not limited to, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. The heating rate of carbonization is 0.1°C / min to 10°C / min. In some embodiments, the heating rate of carbonization is 0.5°C / min to 8°C / min. In some embodiments, the heating rate of carbonization is 3°C / min to 7°C / min. In some embodiments, the heating rate of carbonization is 5°C / min. As an example, the heating rate of carbonization can be, but is not limited to, 0.1°C / min, 0.5°C / min, 0.8°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min.

[0060] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0061] Example 1

[0062] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0063] (I) Coarsely crush sub-bituminous coal to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v 50 is 6 μm coal powder, 85 wt.% potassium hydroxide is dissolved in water, and then the coal powder is added and mixed in a mixer, the speed of the mixer is 200 r / min, the stirring time is 2 h, and then dried in an oven at 85° C. for 24 h to obtain a mixture, wherein the mass ratio of coal powder, 85 wt.% potassium hydroxide and water is 1:0.2:1.5;

[0064] (II) placing the mixed material in a furnace and performing low-temperature carbonization activation in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 700° C., the heating rate of the low-temperature carbonization activation is 5° C. / min, and the holding time is 2 h;

[0065] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.6:1.5 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:4 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0066] (IV) placing the second precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1400° C., a carbonization heating rate of 5° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0067] Example 2

[0068] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0069] (I) Coarsely crush sub-bituminous coal to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v50 is 6 μm coal powder, 85 wt.% potassium hydroxide is dissolved in water, and then the coal powder is added and mixed in a mixer, the speed of the mixer is 200 r / min, the stirring time is 2 hours, and then dried in an oven at 85° C. for 24 hours to obtain a mixture, wherein the mass ratio of coal powder, 85 wt.% potassium hydroxide and water is 1:0.3:1.5;

[0070] (II) placing the mixed material in a furnace and performing low-temperature carbonization activation in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 700° C., the heating rate of the low-temperature carbonization activation is 5° C. / min, and the holding time is 2 h;

[0071] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.6:1.5 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:4 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0072] (IV) placing the second precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1400° C., a carbonization heating rate of 5° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0073] Figure 1 The preparation process flow chart of this embodiment is shown.

[0074] Figure 2 The SEM image of the coal-based hard carbon negative electrode material prepared in this embodiment is shown. It can be seen from the figure that the surface of the material block is rough, exposing more sodium storage active sites; the particle size distribution is appropriate and the filling is dense, which is conducive to the material obtaining a higher compaction density.

[0075] Example 3

[0076] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0077] (I) Coarsely crush sub-bituminous coal to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v 50 is 6 μm coal powder, 85 wt.% potassium hydroxide is dissolved in water, and then the coal powder is added and mixed in a mixer, the speed of the mixer is 200 r / min, the stirring time is 2 hours, and then dried in an oven at 85° C. for 24 hours to obtain a mixture, wherein the mass ratio of coal powder, 85 wt.% potassium hydroxide and water is 1:0.4:1.5;

[0078] (II) placing the mixed material in a furnace and performing low-temperature carbonization activation in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 700° C., the heating rate of the low-temperature carbonization activation is 5° C. / min, and the holding time is 2 h;

[0079] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.6:1.5 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:4 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0080] (IV) placing the second precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1400° C., a carbonization heating rate of 5° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0081] Example 4

[0082] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0083] (I) Coarsely crush sub-bituminous coal to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v 50 is 6 μm coal powder, 85 wt.% potassium hydroxide is dissolved in water, and then the coal powder is added and mixed in a mixer, the speed of the mixer is 200 r / min, the stirring time is 2 hours, and then dried in an oven at 85° C. for 24 hours to obtain a mixture, wherein the mass ratio of coal powder, 85 wt.% potassium hydroxide and water is 1:0.3:1.5;

[0084] (II) placing the mixed material in a furnace and performing low-temperature carbonization activation in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 800° C., the heating rate of the low-temperature carbonization activation is 5° C. / min, and the holding time is 2 h;

[0085] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.6:1.5 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:4 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0086] (IV) placing the second precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1400° C., a carbonization heating rate of 5° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0087] Example 5

[0088] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0089] (I) Coarsely crush the lignite to a particle size D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v 50 is 5 μm coal powder, 99wt.% sodium hydroxide is dissolved in water, and then the coal powder is added and mixed in a mixer, the speed of the mixer is 150r / min, the stirring time is 3h, and then dried in an oven at 85°C for 24h to obtain a mixture, wherein the mass ratio of coal powder, 99wt.% sodium hydroxide and water is 1:0.3:1.5;

[0090] (II) placing the mixed material in a furnace and performing low-temperature carbonization activation in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 650° C., the heating rate of the low-temperature carbonization activation is 7° C. / min, and the holding time is 2.5 h;

[0091] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.8:10 to a reactor, and reacting at 62°C for 8h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:3 to a reactor, and reacting at 78°C for 5h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0092] (IV) placing the second precursor in a furnace and carbonizing it in an argon atmosphere at a carbonization temperature of 1500° C., a carbonization heating rate of 8° C. / min, and a holding time of 1.8 h to obtain a coal-based hard carbon negative electrode material.

[0093] Example 6

[0094] This embodiment is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0095] (I) Roughly crush the anthracite to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v50 is 7 μm coal powder, 85 wt.% potassium hydroxide is dissolved in water, and then the coal powder is added and mixed in a mixer, the speed of the mixer is 260 r / min, the stirring time is 1 hour, and then dried in an oven at 85° C. for 24 hours to obtain a mixture, wherein the mass ratio of coal powder, 85 wt.% potassium hydroxide and water is 1:0.1:1;

[0096] (II) placing the mixed material in a furnace and performing low-temperature carbonization activation in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 820° C., the heating rate of the low-temperature carbonization activation is 3° C. / min, and the holding time is 1.5 h;

[0097] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.1:2 into a reactor, and reacting at 75°C for 5h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:5 into a reactor, and reacting at 68°C for 6h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0098] (IV) placing the second precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1350° C., a carbonization heating rate of 4° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0099] Comparative Example 1

[0100] This comparative example is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0101] (I) Coarsely crush sub-bituminous coal to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v 50 is 6μm coal powder;

[0102] (II) placing pulverized coal in a furnace and performing low-temperature carbonization in a nitrogen atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization is 700° C., the heating rate of the low-temperature carbonization activation is 5° C. / min, and the holding time is 2 h;

[0103] (III) adding the first precursor, 38wt.% hydrochloric acid and water in a mass ratio of 1:0.6:1.5 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:4 into a reactor, and reacting at 70°C for 6h, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24h to obtain a second precursor;

[0104] (IV) placing the second precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1400° C., a carbonization heating rate of 5° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0105] Comparative Example 2

[0106] This comparative example is a method for preparing a coal-based hard carbon negative electrode material, comprising the following steps:

[0107] (I) Coarsely crush sub-bituminous coal to a particle size of D v 100 is 0.8 cm, and is placed in an oven at 85 °C for 24 h. The dried coal is crushed to obtain a particle size D v 50 is 6μm coal powder;

[0108] (II) adding pulverized coal, 38 wt.% hydrochloric acid and water in a mass ratio of 1:0.6:1.5 to a reactor, and reacting at 70°C for 6 hours, cooling to room temperature and filtering under negative pressure to obtain an acid-washed material; adding the acid-washed material and water in a mass ratio of 1:4 to a reactor, and reacting at 70°C for 6 hours, cooling to room temperature and filtering under negative pressure, repeatedly washing with water until the filtrate is neutral, and drying in an oven at 85°C for 24 hours to obtain a first precursor;

[0109] (III) placing the first precursor in a furnace and carbonizing it in a nitrogen atmosphere at a carbonization temperature of 1400° C., a carbonization heating rate of 5° C. / min, and a holding time of 2 h to obtain a coal-based hard carbon negative electrode material.

[0110] Comparative Example 3

[0111] The "mass ratio of coal powder, 85wt.% potassium hydroxide and water is 1:0.3:1.5" in step (I) of Example 2 is changed to "the mass ratio of coal powder, 85wt.% potassium hydroxide and water is 1:1:1.5", and the rest is the same as Example 2.

[0112] Comparative Example 4

[0113] The "mass ratio of coal powder, 85wt.% potassium hydroxide and water is 1:0.3:1.5" in step (I) of Example 2 is changed to "the mass ratio of coal powder, 85wt.% potassium hydroxide and water is 1:0.005:1.5", and the rest is the same as Example 2.

[0114] Comparative Example 5

[0115] In step (II) of Example 2, "the temperature of low-temperature carbonization activation is 700°C" is changed to "the temperature of low-temperature carbonization activation is 380°C", and the rest is the same as Example 2.

[0116] Comparative Example 6

[0117] In step (II) of Example 2, "the temperature of low-temperature carbonization activation is 700°C" is changed to "the temperature of low-temperature carbonization activation is 1050°C", and the rest is the same as Example 2.

[0118] Comparative Example 7

[0119] The step (III) of Example 2, "add the first precursor, 38 wt.% of hydrochloric acid and water in a mass ratio of 1:0.6:1.5 to the reactor" is changed to "add the first precursor, 38 wt.% of nitric acid and water in a mass ratio of 1:0.6:1.5 to the reactor", and the rest is the same as Example 2.

[0120] The physical and chemical properties of the coal-based hard carbon negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 7 were tested, and they were made into half-cells for electrochemical performance testing. The half-cell preparation process and test conditions are as follows, and the test results are shown in Table 1.

[0121] Specific surface area:

[0122] The nitrogen adsorption / desorption isotherms of the materials were obtained by Micromeritics ASAP 2460 analyzer, and their specific surface areas were calculated by the BET method.

[0123] Ash content:

[0124] The ash content of the material is determined according to the national standard GB / T 1429-2009 “Determination of ash content of carbon materials”.

[0125] Element content:

[0126] The element contents of the materials were determined by inductively coupled plasma-mass spectrometry (ICP-MS).

[0127] Preparation of half-cell:

[0128] The active material and the binder carboxymethyl cellulose (CMC) were uniformly dispersed in deionized water at a mass ratio of 95:5 to obtain a slurry, which was then coated on a copper foil. After being dried in a vacuum oven at 120°C for 12 hours, the slurry was cut into discs with a diameter of 1 cm. The surface density of the active material loaded on the discs was 0.8-1.0 mg / cm 2 In a glove box with argon atmosphere (H2O < 0.1 ppm, O2 < 0.1 ppm), CR2032 button cells were assembled using metallic sodium as the counter electrode and 1 M NaClO4 dissolved in 1:1 volume ratio of ethylene carbonate (EC) and diethyl carbonate (DEC) and 5% fluoroethylene carbonate (FEC) as the electrolyte.

[0129] Specific capacity:

[0130] The charge and discharge tests were carried out in the potential range of 0 to 2 V, and the charge capacity (sodium removal) was taken as the reversible capacity.

[0131] Platform capacity share:

[0132] During the charging process, the ratio of the capacity with a potential less than 0.1V to the total capacity.

[0133] First Coulombic efficiency:

[0134] The ratio of the charge capacity (sodium removal) to the discharge capacity (sodium insertion) during the first cycle.

[0135] Table 1. Test results of coal-based hard carbon negative electrode materials prepared in Examples 1 to 6 and Comparative Examples 1 to 7

[0136]

[0137] See the data in Table 1 for details. The test results of Comparative Examples 1 and 2 show that the hard carbon obtained by purifying the raw material with hydrochloric acid has a higher ash content, and has a lower specific capacity and first efficiency. From the results of Comparative Examples 1, Comparative Examples 3-4 and Examples 1-3, it can be seen that with the increase in the amount of potassium hydroxide, the specific surface area of ​​the final hard carbon will increase. This is mainly because excessive etching makes it difficult to close the open pores. Generally, a more suitable specific surface area contributes to a higher first coulomb efficiency; and the ash content decreases significantly, which is mainly reflected in the reduction of the content of elements such as iron, silicon, and aluminum. The results of Comparative Examples 5-6, Examples 2 and 4 show that the higher the low-temperature carbonization activation temperature, the larger the specific surface area of ​​the hard carbon produced, but the lower the ash content, indicating that the activity of potassium hydroxide is enhanced. Compared with Comparative Example 1, the specific capacity and platform capacity ratio of Examples 1-4 are significantly improved, indicating that they have more closed pores.

[0138] From the comparison between Example 2 and Comparative Example 7, it can be seen that when hydrochloric acid is replaced by nitric acid, the ash content of the hard carbon decreases slightly, but the specific surface area increases. This may be because nitric acid oxidizes and modifies the carbon surface during the pickling process, and the oxygen-containing functional groups inhibit the orderly growth of carbon microcrystals during carbonization, resulting in more defects, so that Comparative Example 7 shows a reduced first effect. In summary, Example 2 is the optimal method for preparing coal-based hard carbon negative electrode materials for sodium power in the present invention.

[0139] Further by Figure 3It can be seen that the figure shows the microstructural evolution of coal-based hard carbon negative electrode materials prepared by the preparation methods of Comparative Example 2, Comparative Example 1 and Example 2 from top to bottom. Among them, the preparation method of Comparative Example 2 is to purify the raw material end, and hydrochloric acid purification can only remove salts containing calcium, magnesium and the like on the surface of the coal powder, and it is difficult to remove minerals such as silicon and aluminum on the surface and impurities in the bulk phase. The preparation method of Comparative Example 1 first carbonizes the coal powder at low temperature, and the impurities therein will undergo thermal decomposition or crystal phase transformation, and will be transformed from hydrochloric acid insoluble substances to hydrochloric acid soluble substances, and then the surface impurities can be removed by hydrochloric acid purification. The preparation method of Example 2 first mixes the coal powder with potassium hydroxide and then carbonizes it at low temperature. On the one hand, the molten potassium hydroxide will etch the carbon skeleton to produce a porous structure, and the specific surface area of ​​the material will increase. In the subsequent hydrochloric acid purification process, the large specific surface area is conducive to full contact between the solid and liquid phases. In addition, hydrochloric acid-insoluble minerals such as silicon and aluminum react with potassium hydroxide to form hydrochloric acid soluble substances, thereby effectively removing ash. The surface carbon layers of the purified materials of the above three preparation methods will slide and close during carbonization, while the preparation method of Example 2 of the present invention will form more closed-pore structures, which is beneficial to improving the sodium storage capacity.

[0140] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a coal-based hard carbon negative electrode material, characterized in that: Includes steps: (I) uniformly mixing coal powder, alkali and water and drying the mixture to obtain a mixture, wherein the mass ratio of the coal powder, the alkali and the water is 1:0.01-0.8:1-10; (II) subjecting the mixed material to low-temperature carbonization activation in a first inert atmosphere to obtain a first precursor, wherein the temperature of the low-temperature carbonization activation is 450° C. to 1000° C.; (III) acid-washing, water-washing and drying the first precursor to obtain a second precursor; (IV) carbonizing the second precursor in a second inert atmosphere.

2. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The coal powder is obtained by coarsely breaking, drying and pulverizing the raw coal.

3. The method for preparing a coal-based hard carbon negative electrode material according to claim 2, characterized in that: The invention comprises at least one of the following features (i) to (iv): (i) the raw coal is selected from at least one of anthracite, bituminous coal, sub-bituminous coal and lignite; (ii) The particle size D of the raw coal v 100 is 0.1cm~1.0cm; (iii) the drying temperature of the raw coal is 50°C to 100°C, and the drying time is 12h to 72h; (iv) The raw coal is pulverized in at least one of a jet mill, a roller mill and a mechanical mill.

4. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The invention comprises at least one of the following features (i) to (ii): (1) the base is selected from at least one of sodium hydroxide and potassium hydroxide; (ii) the mixing is carried out in a stirrer, the speed of the stirrer is 50 r / min to 500 r / min, and the stirring time is 0.5 h to 12 h; (iii) the holding time of the low temperature carbonization activation is 0.5h to 10h; (iv) the heating rate of the low temperature carbonization activation is 0.1°C / min to 10°C / min; (5) the acid used for pickling is selected from hydrochloric acid; (vi) the effective content of the acid is 36 wt.% to 38 wt.%; (VII) The pickling temperature is 50°C to 90°C, and the pickling time is 4h to 24h; (VIII) The water washing temperature is 50°C to 90°C, and the water washing time is 0.5h to 5h; (IX) The carbonization temperature is 1100°C to 1600°C, and the holding time is 1h to 10h; (10) The heating rate of the carbonization is 0.1°C / min to 10°C / min; (XI) In step (I) and step (III), the drying temperature is independently 50°C to 100°C, and the drying time is independently 12h to 72h; (XII) The first inert atmosphere and the second inert atmosphere are each independently selected from at least one of nitrogen, argon and helium.

5. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The step (I) comprises first dissolving alkali in the water, then adding the coal powder, stirring evenly and then drying to obtain a mixture.

6. The method for preparing a coal-based hard carbon negative electrode material according to claim 5, characterized in that: The invention comprises at least one of the following features (1) to (2): (1) The effective content of the alkali is greater than or equal to 85wt.%; (2) Particle size D of the coal powder v 50 is 2μm~15μm.

7. The method for preparing a coal-based hard carbon negative electrode material according to claim 1, characterized in that: The acid washing comprises reacting the first precursor, the acid and water and filtering once to obtain an acid washed material, and the water washing comprises repeatedly washing the acid washed material in water and filtering twice until the filtrate is neutral.

8. The method for preparing a coal-based hard carbon negative electrode material according to claim 7, characterized in that: The invention comprises at least one of the following features (a) to (c): (a) the mass ratio of the first precursor, the acid and the water is 1:0.01-0.8:1-10; (b) the mass ratio of the pickling material to the water is 1:1 to 25; (c) The primary filtration and the secondary filtration are each independently selected from negative pressure filtration, positive pressure filtration or centrifugal filtration.

9. A coal-based hard carbon negative electrode material, characterized in that: The preparation method is described in any one of claims 1 to 8.

10. A sodium ion battery comprising a positive electrode material, a negative electrode material and an electrolyte, characterized in that: The negative electrode material is the coal-based hard carbon negative electrode material according to claim 9.

Citation Information

Patent Citations

  • Coal-based hard carbon negative electrode material of sodium ion battery, preparation method and application thereof

    CN113381013A

  • Coal-based hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN118183739A

  • Method for preparing coal-based hard carbon negative electrode material through alkali treatment modification and application

    CN115650228A

  • Hard carbon negative electrode material and preparation method and application thereof

    CN118545697A

Cited By

  • Preparation method of coal-based hard carbon negative electrode material of sodium ion battery

    CN121044573A

  • Coal-based carbon negative electrode material, preparation method thereof and full-carbon-based lithium ion capacitor

    CN121282016A